2021
DOI: 10.1016/j.molmet.2021.101256
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic epistasis of Hnf4α and FoxO1 metabolic networks through enhancer interactions in β-cell function

Abstract: Objective Genetic and acquired abnormalities contribute to pancreatic β-cell failure in diabetes. Transcription factors Hnf4α (MODY1) and FoxO1 are respective examples of these two components and act through β-cell-specific enhancers. However, their relationship is unclear. Methods In this report, we show by genome-wide interrogation of chromatin modifications that ablation of FoxO1 in mature β-cells enriches active Hnf4α enhancers according to a HOMER analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…We reckoned that this was compensatory in nature, and that in the absence of FoxO1, HNF4α compensates for some of its functions. But when we tested the hypothesis in vivo we found the opposite result [46]. Combined ablation of FoxO1 and HNF4α reversed the β-cell defects associated with single mutations of either gene, indicating that their interactions are antagonistic rather than compensatory.…”
Section: Genes Of Type 2 Diabetesmentioning
confidence: 87%
See 1 more Smart Citation
“…We reckoned that this was compensatory in nature, and that in the absence of FoxO1, HNF4α compensates for some of its functions. But when we tested the hypothesis in vivo we found the opposite result [46]. Combined ablation of FoxO1 and HNF4α reversed the β-cell defects associated with single mutations of either gene, indicating that their interactions are antagonistic rather than compensatory.…”
Section: Genes Of Type 2 Diabetesmentioning
confidence: 87%
“…In our experiments with FoxO1 and HNF4α, gene expression analyses revealed that different gene families were regulated by these two transcription factors with different modalities. For example, the glycolysis pathway was regulated through antagonistic epistasis (i.e., the two factors had opposite effects), and the protocadherin gene family by synergistic epistasis (i.e., the two factors had additive effects) [46].…”
Section: Genes Of Type 2 Diabetesmentioning
confidence: 99%
“…In contrast to Akr1c19, we did not observe HNF1a-induced promoter activation of Akr1c12 and 13 in HEK293 cells ( S1 Fig ). In previous work, we have shown that the three FoxO genes (1, 3a, and 4) are required to maintain the MODY-related gene network [ 10 , 28 ]. Therefore, to investigate the involvement of FoxO1 in the regulation of Akr1c19 by HNF1a, we co-expressed HNF1a and a dominant negative FoxO1 D256, a truncated mutant lacking the transactivation domain [ 23 ], in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, loss of β-cell identity leads to increased glycolysis by disrupting key β-cell metabolic genes including Slc2a2 , Gck , Hk1 , Hk2 , and Ldha [ 42 , 71 ]. Recent evidence demonstrates that FoxO1 suppresses glycolytic genes and thereby protects β cells from excess glycolysis and dysfunction [ [72] , [73] , [74] ]. These studies further support the hypothesis that attenuation of hyperactive glycolysis prevents the impairment of β-cell function and identity.…”
Section: Discussionmentioning
confidence: 99%